2013
DOI: 10.1179/1743282012y.0000000029
|View full text |Cite
|
Sign up to set email alerts
|

Life-form adaptations and substrate availability explain a 100-year post-grazing succession of bryophyte species in the Moricsala Strict Nature Reserve, Latvia

Abstract: AS 'Latvijas valsts meži', Riga, LatviaBryophyte species composition, richness and life-form distributions were studied in a succession after termination of land-use as meadows and pasture in the Moricsala Strict Nature Reserve. Detailed lists of bryophyte species in various vegetation types, which were produced in the early 1900s by Karl Reinhold Kupffer, were compared with those prepared from 2006 to 2010 to determine changes in species composition. Colonisations and extinctions of bryophyte species and life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Higher representation of species with more complex life-forms (such as smooth mat, rough mat, tall turf) and long-term life-strategies (like perennial stayer) are consistent with previous studies about bryophyte adaptation to moist microclimate and shadier conditions within unmanaged forest habitats (Strazdiòa et al, 2013). Fraxinus excelsior, Tilia cordata, and Quercus robur forest stands provided more suitable environment for life-form and life-strategy richness than other stands, most probably due to more diverse tree layer structure and composition, presence of phorophytes of different size and age, as well as stand continuity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Higher representation of species with more complex life-forms (such as smooth mat, rough mat, tall turf) and long-term life-strategies (like perennial stayer) are consistent with previous studies about bryophyte adaptation to moist microclimate and shadier conditions within unmanaged forest habitats (Strazdiòa et al, 2013). Fraxinus excelsior, Tilia cordata, and Quercus robur forest stands provided more suitable environment for life-form and life-strategy richness than other stands, most probably due to more diverse tree layer structure and composition, presence of phorophytes of different size and age, as well as stand continuity.…”
Section: Discussionsupporting
confidence: 91%
“…Studies of species functional traits like life-strategies or life-forms in Latvia (Strazdiòa et al, 2013;Meþaka and Kirillova, 2019;Ievinsh et al, 2020) and in other countries from the boreal region (Darell and Cronberg, 2011;Michel et al, 2012) have shown that there is different specificity to host tree characteristics and habitat conditions. Some species, especially rare species and indicators of pristine forests, are dependent on large areas of long forest continuity with specific niche abundance (Hedderson, 1992;Söderström, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As with vascular plants, plant traits can provide useful insights into the abilities of species within these life strategies and the associated succession stage; however, relevant trait data are not always available for bryophytes (Cruz de Carvalho et al., 2019; During, 1979). Life form is an important plant trait for succession and has been utilised in several studies (Cruz de Carvalho et al., 2019; Ezer et al., 2019; Strazdiņa et al., 2013). Although there are several classification systems available for bryophytes (Bates, 1998; Magdefrau, 1982), During (1979) suggested that the bryophyte life forms of dendroids, cushions and wefts are restricted to ‘perennial stayers’, therefore arising later in succession, whilst short turfs are usually found amongst ‘short‐lived shuttle species’.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that short turfs and cushions are typical for sunny, dry and xeric habitats, while bryophytes forming mats, wefts, tails and fans dominate humid and shady habitats (Bates, 1998;Kürschner, 2004). Recently, life forms have been used to explain a 100-year-long succession of bryophytes in forest habitat, which was associated with increase of available substrates as well as habitat shading (Strazdiòa et al, 2013). In particular, these changes led to disappearance of compact cushions and short turfs, while smooth and rough mats increased in richness.…”
Section: Introductionmentioning
confidence: 99%